2005
DOI: 10.1183/09031936.04.00138403
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory effects of occupational polypropylene flock exposure

Abstract: The present study evaluated the possible effects of exposure to polypropylene flock on respiratory health and serum cytokines in a cross-sectional study of workers from a plant in Turkey.A total of 50 polypropylene flocking workers were compared to a control group of 45 subjects. All subjects filled out a respiratory questionnaire and underwent a physical examination, a chest radiograph and pulmonary function testing, including single breath carbon monoxide diffusing capacity (DL,CO). Serum interleukin-8 (IL-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 24 publications
(46 reference statements)
0
53
1
4
Order By: Relevance
“…In a nylon flock plant, restriction was observed in 7% of production workers compared to 3% in office workers; the prevalences of low diffusing capacity were 13% and 5%, respectively [Washko et al, 2000]. Among polypropylene flock workers in Turkey, 20% had restriction and 26% had low DL CO , compared to 4.4% and 4.4%, respectively, of non-exposed controls [Atis et al, 2005]. The proportion of restriction among participants in this plant was 7.8%, and 3.9% had low DL CO .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a nylon flock plant, restriction was observed in 7% of production workers compared to 3% in office workers; the prevalences of low diffusing capacity were 13% and 5%, respectively [Washko et al, 2000]. Among polypropylene flock workers in Turkey, 20% had restriction and 26% had low DL CO , compared to 4.4% and 4.4%, respectively, of non-exposed controls [Atis et al, 2005]. The proportion of restriction among participants in this plant was 7.8%, and 3.9% had low DL CO .…”
Section: Discussionmentioning
confidence: 85%
“…The first clusters of flock workers' lung were identified in 1996, in association with nylon flock [Kern et al, 1997[Kern et al, , 1998]. Polyethylene flock has been implicated in a case of flock workers' lung in Spain [Barroso et al, 2002], and polypropylene flock was associated with increased respiratory symptoms in Turkey [Atis et al, 2005]. This article constitutes the first investigation of the health effects of rayon flock exposure.…”
Section: Introductionmentioning
confidence: 96%
“…In a nylon flock plant, restriction was observed in 7% of production workers compared to 3% in office workers; the prevalences of low diffusing capacity were 13% and 5%, respectively [Washko 2000]. Among polypropylene flock workers in Turkey, 20% had restriction and 26% had low DL CO , compared to 4.4% and 4.4%, respectively, of non-exposed controls [Atis 2005]. The proportion of restriction among Hallmark participants was 7.8%, and 3.9% had low DL CO .…”
Section: Discussionmentioning
confidence: 99%
“…A case of flock workers' lung was described in a worker exposed to polyethylene flock in Spain [Barroso 2002]. In Turkey, a cross-sectional study in the polypropylene flock industry showed a 3.6-fold increase in respiratory symptoms in exposed workers compared to unexposed controls [Atis 2005]. …”
Section: Disease Characteristicsmentioning
confidence: 99%
“…Thus, in the 1990s a very severe form of interstitial lung disease, called Ardystil syndrome, affected Spanish and Algerian textile workers who had been engaged in spraying paints that were reputedly non-toxic [22,23]. Another novel pulmonary disease, flock worker's lung, has recently been described in workers exposed to synthetic micro fibres (flock) of nylon [24], polyethylene [25] or polypropylene [26], although such polymeric materials are generally considered to be devoid of significant toxicity. Recently, serious airways disease affected workers from plants producing microwave popcorn ''popcorn worker's lung'' [27,28], probably as a result of their inhalatory exposure to artificial flavouring agents that are ''generally recognised as safe'' [28].…”
Section: New Risksmentioning
confidence: 99%